Fixed low dose versus concentration-controlled initial tacrolimus dosing with reduced target levels in the course after kidney transplantation: results from a prospective randomized controlled non-inferiority trial (slow & low study) - Stumpf, Julian David Christopher; Budde, Klemens; Witzke, Oliver; Sommerer, Claudia; Vogel, Thomas; Schenker, Peter; Woitas, Rainer Peter; Opgenoorth, Mirian; Trips, Evelyn; Schrezenmeier, Eva; Hugo, Christian; Girndt, Matthias; et al. (EClinicalMedicine, 2024)
Background - Optimal initial tacrolimus dosing and early exposure of tacrolimus after renal transplantation is not well studied. - Methods - In this open-label, 6 months, multicenter, randomized controlled, non-inferiority study, we randomly assigned 432 renal allograft recipients to receive basiliximab induction, mycophenolate and steroids and either standard prolonged-release tacrolimus (trough levels: 7-9 ng/ml; Standard Care arm), or an initial 7-day fixed 5 mg/day dose of prolonged-release tacrolimus followed by lower tacrolimus predose levels (trough levels: 5-7 ng/ml; Slow & Low arm). The primary end point was the combined incidence rate of biopsy-proven acute rejections (BPAR; including borderline), graft failure, or death at 6 months with a non-inferiority margin of 12.5%. (EudraCT-Nr: 2013-001770-19. - Findings - The combined primary endpoint in the Slow & Low arm was non-inferior compared to the Standard Care arm (22.1% versus 20.7%; difference: 1.4%, 90% CI −5.5% to 8.3%). The overall rate of BPAR including borderlines was similar (Slow & Low 17.4% versus Standard Care 16.6%). Safety parameters such as delayed graft function, kidney function, donor specific HLA-antibodies, infections, or post-transplantation diabetes mellitus did not differ. - Interpretation - This is the first study to show that an initial fixed dose of 5 mg per day followed by lower tacrolimus exposure is non-inferior compared to standard tacrolimus therapy and equally efficient and safe within 6 months after renal transplantation. These data suggest that therapeutic drug monitoring for prolonged release tacrolimus can be abandoned until start of the second week after transplantation. - Funding - Investigator-initiated trial, financial support by Astellas Pharma GmbH.
Online verfügbar: 22. Dezember 2023
Gesehen am 10.05.2024